Poetics of translation of novel of Іliyas Esenberlin «Scythian mirages» (Eurasian Journal of Philology Science and Education, 2016)
In the article the poetics of translation of the well-known Kazakh writer of Iliyas Esenberlin are examined the «Scythian mirages». Iliyas Esenberlin is an exactly that writer that on a todays day wrote most of novels from all Kazakh writers, what and known in history of Kazakh literature. His works are deeply estimated by readers. In recent year work of the Kazakh writers very often translated into other languages and find the readers. One of such works novel of Iliyas Esenberlin the «Scythian mirages». Roman that consists of two parts lets know that an author is deeply an industrious and purposeful man. Certainly, not every translator of осмеливаетя to take up translation of work, where the question is about deep history, since scythian times, where meet great number of archaeological terms, with high aesthetics and deep sense nature is described. But however, translation of U. Dombrovski and N. Platonova can be estimated however bad. Translation is given to the reader by simple, accessible, clear.
Keywords: scythian; mirages; novel; poetics; translation; literature; archaeology; philosophy.